Evangelho segundo Racionais MC'S: ressignificações religiosas, políticas e estético-musicais nas narrativas do rap - Takahashi, Henrique Yagui (2014)
The present work consists in a study concerning the ressignifications in the narratives of Racionais MC s group of rap about the daily life of the urban peripheries in the city of São Paulo, during the years 1990 to 2000. These ressignifications about the peripheral dayafter- day would be in three aspects: religious a narrative composition of the rappers using the moral and ethical Christian notions, reviving a biblical narrative, more specifically of Livro Êxodo, and Livro Gênesis and the Jesus Christ, thus presenting a relevance of the peripheral pentecostal universe; politic the rap s subversive and critical bias, arising from the American black leaders discourse such as Malcolm X s, the Brazilian re-democratization process with political participation of the popular classes, and the hip-hop as political, cultural and artistic critic movement to the injustices and social inequalities in the urban peripheries engendered by capitalism and racism; and esthetic-musical through the notion of sample, audible clipping of a music or environment sounds (for example a car exhaust s noise), that composed with other musical elements would constitute the sonority while rap s expressivity constitutive elements, using mainly the black aesthetic-musical genres such as: funk, disco, gospel, soul, samba and pagode. Based on the albums Sobrevivendo no inferno [Surviving in Hell] (1997), and Nada como um dia após outro dia [Nothing as One Day after Another Day] (2002), I shall present their songs as narratives that hybridize political, religious and esthetic-musical elements, thus, establishing a Gospel according to Racionais MC s.